2012
DOI: 10.14245/kjs.2012.9.3.181
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study between a Curved and a Wedge PEEK Cage for Single-level Anterior Cervical Discectomy and Interbody Fusion

Abstract: ObjectiveThis study evaluated the efficiency of a curved polyetheretherketone (PEEK) cage in comparison with a wedge PEEK cage according to radiologic and clinical outcomes in patients with cervical degenerative disease.MethodsA total of 37 patients who suffering from cervical disc disease with radiculopathy or myelopathy were reviewed retrospectively. Seventeen patients were underwent anterior cervical discectomy and interbody fusion with a curved shape PEEK cage (curved cage group), and twenty patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Clinical studies have shown that the mismatch between BEP and GB triggers complications, including nonunion and cage subsidence (Kim et al, 2012;Hu et al, 2021), and the mechanism of this phenomenon has been well explained. Specifically, biomechanical studies proved that the mismatch between BEP and GB changes the local load transmission pattern, and stress concentration can be observed on both the cranial and caudal sides of BEP and sub-BEP cancellous bone (Agarwal et al, 2013;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have shown that the mismatch between BEP and GB triggers complications, including nonunion and cage subsidence (Kim et al, 2012;Hu et al, 2021), and the mechanism of this phenomenon has been well explained. Specifically, biomechanical studies proved that the mismatch between BEP and GB changes the local load transmission pattern, and stress concentration can be observed on both the cranial and caudal sides of BEP and sub-BEP cancellous bone (Agarwal et al, 2013;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…2012 studied curved and wedged shaped PEEK cages and suggested that implant shape was an important risk factor. [35] Similarly, Le et al. 2012 found that wider cages significantly mitigated the risk of subsidence while length was not significant.…”
Section: Discussionmentioning
confidence: 98%
“…To overcome these drawbacks, a novel porous n-HA/PA66 composite has been developed in recent years [24][25][26][27]. More effort Cage subsidence in ACDF can be influenced by many factors, including end plate preparation, postoperative cervical motion, cage design and material properties, implantation of the anterior cervical plate, and bone mineral density or age [28][29][30][31]. This case-matched study was performed to reduce the confounding factors as much as logically and reasonably possible to examine the impact of the subsidence of material characteristics, and the two groups were well matched.…”
Section: Discussionmentioning
confidence: 99%